2003
DOI: 10.1038/sj.bmt.1704347
|View full text |Cite
|
Sign up to set email alerts
|

Infections among allogeneic bone marrow transplant recipients in India

Abstract: Summary:Infections are a major cause of morbidity and mortality in patients undergoing high-dose therapy and allogeneic bone marrow transplantation (BMT) despite prophylaxis, use of growth factors and newer antimicrobial drugs. We report the clinical profile of infections among 297 patients who underwent 304 allogeneic transplants between 1986 and December 2001. All patients developed febrile neutropenia. There were 415 documented infections among 304 transplants. This included bacterial (34.9%), viral (42.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
2
38
3
1
Order By: Relevance
“…During the first month post-HSCT, immune reconstitution is not complete and patients are extremely susceptible to bacterial, viral, and fungal infections [24,51]. One study indicated that over 80% of patients had either clinical or microbiologically significant bacterial, fungal, or viral infections during the neutropenic stage post-HSCT [40]. Aspergillosis is an especially dangerous threat to both allogeneic and autologous HSCT recipients during the pre-engraftment period [51].…”
Section: Infectious Hsct Complicationsmentioning
confidence: 99%
“…During the first month post-HSCT, immune reconstitution is not complete and patients are extremely susceptible to bacterial, viral, and fungal infections [24,51]. One study indicated that over 80% of patients had either clinical or microbiologically significant bacterial, fungal, or viral infections during the neutropenic stage post-HSCT [40]. Aspergillosis is an especially dangerous threat to both allogeneic and autologous HSCT recipients during the pre-engraftment period [51].…”
Section: Infectious Hsct Complicationsmentioning
confidence: 99%
“…Among these patients, the prevalence of TB after allo-SCT was B10%, a rate similar to or higher than that reported from centers in TB endemic regions. 6,10 Overall, 20% (4/20) of foreign-born patients with positive mycobacterial cultures had TB compared to 0% (0/34) of US-born patients (Po0.05).…”
mentioning
confidence: 99%
“…A recent report from India described Tuberculosis was seen in 1.7% of pediatrics transplant patients [2]. Another report from India Tuberculosis was documented in 2.3% of the transplant patients [3]. They can presents with fatal sepsis as reported by Kindler, T et al [4].…”
Section: Discussionmentioning
confidence: 96%
“…Fungal infection with aspergillus is common in BMT recipient. The incidence of fungal infection was 15.9% and commonly due to (69.7%) aspergillus species [3].…”
Section: Discussionmentioning
confidence: 99%